2023
DOI: 10.1111/jdv.18727
|View full text |Cite
|
Sign up to set email alerts
|

Spesolimab, an anti‐interleukin‐36 receptor antibody, in patients with moderate‐to‐severe atopic dermatitis: Results from a multicentre, randomized, double‐blind, placebo‐controlled, phase IIa study

Abstract: Background Atopic dermatitis (AD) is a chronic relapsing inflammatory skin disease, and there is increasing evidence that the interleukin (IL)‐36 pathway may play a role in the pathogenesis of AD. Objectives To evaluate the efficacy and safety of spesolimab, a novel anti‐IL‐36 receptor antibody, in adult patients with moderate‐to‐severe AD. Methods In this phase IIa study, 51 eligible patients were randomized 2:1 to receive intravenous doses of spesolimab 600 mg or placebo every 4 weeks. The primary endpoint w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…Spesolimab did not show a significant difference in efficacy compared with placebo in a multicenter phase IIa randomized controlled trial on 51 patients with moderate‐to‐severe atopic dermatitis. Spesolimab was well tolerated, and no new clinically relevant adverse effects were reported 16 . Further development for atopic dermatitis was terminated.…”
Section: Efficacymentioning
confidence: 99%
See 4 more Smart Citations
“…Spesolimab did not show a significant difference in efficacy compared with placebo in a multicenter phase IIa randomized controlled trial on 51 patients with moderate‐to‐severe atopic dermatitis. Spesolimab was well tolerated, and no new clinically relevant adverse effects were reported 16 . Further development for atopic dermatitis was terminated.…”
Section: Efficacymentioning
confidence: 99%
“…15 Atopic dermatitis-related Staphylococcus aureus infection promotes cutaneous inflammation through the IL-36-mediated T-cell response. 16 Many studies have reported enhanced IL-36 activity in the lesional skin of atopic dermatitis but not to the extent seen in psoriasis. 17 The expression of IL-36 is higher in chronic AD lesions compared with acute lesions, suggesting the probable role of IL-36 in disease progression.…”
Section: Role Of Il-36 In Inflammatory Skin Conditionsmentioning
confidence: 99%
See 3 more Smart Citations